Yb3+ and Yb3+/Er3+ doping for near-infrared emission and improved stability of CsPbCl3 nanocrystals. Issue 37 (10th September 2018) - Zhang, Xiangtong; Zhang, Yu; Zhang, Xiaoyu; Yin, Wenxu; Wang, Yu; Wang, Hua; Lu, Min; Li, Zhiyang; Gu, Zhiyong; Yu, William W.
Abstract : Doping Yb 3+ or Er 3+ ions into CsPbCl3 NCs expands their emissions to the infrared region and improves their stability. Abstract : Lead halide perovskite nanocrystals (NCs) exhibit excellent tunable emissions covering the entire visible spectral region, but they do not emit near-infrared (NIR) light. We synthesized rare earth element doped CsPbCl3 NCs for NIR emission. The Yb 3+ doped CsPbCl3 NCs emitted strong 986 nm NIR light; the Yb 3+ /Er 3+ co-doped CsPbCl3 NCs emitted at 1533 nm. The total photoluminescence quantum yield (PL QY) of the CsPbCl3 NCs changed from 5.0% to 127.8% upon incorporating 2.0% Yb 3+, a factor of 25.6 times enhancement. The material's stability was tested under continuous ultraviolet (365 nm) irradiation. The doped CsPbCl3 NCs exhibited a better stability than the undoped one. The PL intensity of the undoped CsPbCl3 NCs dropped to 20% of the initial value in 27 h, while the doped one took 85 h.